2005
DOI: 10.1093/annonc/mdi007
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose interleukin-11 in patients with bone marrow failure: update of the M. D. Anderson Cancer Center experience

Abstract: Low-dose IL-11 has activity in patients with BMF and is generally well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…However, 1 patient in the second study had a transient ischemic attack after completing treatment, and 1 patient developed atrial fibrillation/supraventricular tachycardia. 82,83 Other cardiovascular events, such as arrhythmias and pulmonary edema, also have been observed. 84 Oprelvekin also has been associated with allergic and hypersensitivity reactions, including anaphylaxis, and serious fluid retention, which has been fatal in some patients.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…However, 1 patient in the second study had a transient ischemic attack after completing treatment, and 1 patient developed atrial fibrillation/supraventricular tachycardia. 82,83 Other cardiovascular events, such as arrhythmias and pulmonary edema, also have been observed. 84 Oprelvekin also has been associated with allergic and hypersensitivity reactions, including anaphylaxis, and serious fluid retention, which has been fatal in some patients.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…82 It is approved by the FDA for the prevention of severe thrombocytopenia after myelosuppressive chemotherapy in patients with nonmyeloid malignancies who are at high risk for this toxicity. 82 Two small, single-arm studies have explored its use in patients with bone marrow failure, including those with bone marrow failure caused by MDS. 82,83 In the pilot study, median platelet counts at baseline were 12 3 10 9 /L, and 38% of patients showed a platelet response.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…thrombopoietin mimetics) are being investigated as alternatives to platelet transfusions (5,6). Based on the duration and severity of thrombocytopenia, neonates with sepsis and/or NEC could be potential candidates for therapy with thrombopoietic growth factors.…”
mentioning
confidence: 99%